Tindak Pidana Pengolahan, dan Peredaran dan atau Pemasaran Hasil Perkebunan yang Membahayakan Kesehatan dan Keselamatan Manusia - Yovi Wicaksana Putra; Kartina Pakpahan; Lusi Feny Panjaitan; Arta Hot Manullang (Mahesa Research Center, 2020)
The Indonesian country is rich in farmed communities, especially agricultural livelihoods. It is not rare that farm yields fail to meet its quality standards, satisfy the health and safety of masvardized research purposes, which are assessed the form of legal protection to consumers, plantation criteria, punishments that are given to criminal processing, distribution and or or marketing of health and safety estates. Using normatif juridical research methods by studying the major issues based on data obtained. The study USES analytical descriptive properties to give swift response to the objects being examined. The conclusion that the processing, distribution and marketing of plantation products has been established in article 77 Jo 110 of the 2014 section no. 39 on plantation and section no. 8 of 1999 on consumer protection. Food and drug administration regulation no. 28 stages 2019 of food-care agents. The use of additives or helper that is used does not fit security requirements and quality or use that exceeds have adverse effects on human health and safety. At the risk of public health and safety, non-performing consumers will be punished by the da's criminal penalties